BALANCED CONTENT ALLOCATION SCHEME FOR PEERSERVICE AREA CDN ARCHITECTURE FOR IPTV SERVICES (Journal of Information and Communication Technology, 2012)
One of the main problems in IPTV technology is how to manage the huge amount of multimedia contents efficiently to meet the demands of users especially for Video on Demand (VoD) services. Content Distribution Networks (CDN) are used to solve this problem but the problem of load imbalance among servers still exists due to the dynamic changes in contents and user interests in an IPTV environment. In the VoD context, many content storage management architecture models are proposed: single point, hierarchal, distributed, and service peer area architectures. In the this paper we choose peer-service area architecture for CDN to study the load imbalance problem and try to handle it by modifying peer-service area architecture and proposing a balanced content allocation scheme that solves the load imbalance problem by replicating the contents based on their popularity. Experimental results show that this proposed allocation scheme can maintain the load balancing among servers and avoid over/under utilization of servers.